limit x tends to 4 √(x+5) -3 ÷ x-4
Answers
Answered by
7
so now let see one example
what is the the limit of
![\frac{ \sqrt{x + 5 } - 3}{x - 4} \frac{ \sqrt{x + 5 } - 3}{x - 4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7Bx+%2B+5+%7D++-+3%7D%7Bx+-+4%7D+)
as x approaches 4
sol .
let's multiplying both side numerator and denominator of the expression by
![\sqrt{x + 5} + 3 \sqrt{x + 5} + 3](https://tex.z-dn.net/?f=+%5Csqrt%7Bx+%2B+5%7D++%2B+3)
to get rid to undefined
![\frac{0}{0} \frac{0}{0}](https://tex.z-dn.net/?f=+%5Cfrac%7B0%7D%7B0%7D+)
value
assuming is not equal to 4
then
![\frac{ \sqrt{x + 5} - 3}{x - 4} = \frac{ \sqrt{x + 5} - 3}{x - 4} =](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7Bx+%2B+5%7D++-+3%7D%7Bx+-+4%7D++%3D+)
![= \frac{ (\sqrt{x + 5} - 3).( \sqrt{x + 5} + 3}{(x - 4).( \sqrt{x + 5} + 3)} = \frac{ (\sqrt{x + 5} - 3).( \sqrt{x + 5} + 3}{(x - 4).( \sqrt{x + 5} + 3)}](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7B+%28%5Csqrt%7Bx+%2B+5%7D++-+3%29.%28+%5Csqrt%7Bx+%2B+5%7D++%2B+3%7D%7B%28x+-+4%29.%28+%5Csqrt%7Bx+%2B+5%7D++%2B+3%29%7D+)
![= \frac{x + 5 - 9}{{(x - 4).( \sqrt{x + 5} + 3)} \: } = \frac{x - 4}{{(x - 4).( \sqrt{x + 5} + 3)} \: } = \frac{x + 5 - 9}{{(x - 4).( \sqrt{x + 5} + 3)} \: } = \frac{x - 4}{{(x - 4).( \sqrt{x + 5} + 3)} \: }](https://tex.z-dn.net/?f=+%3D+%5Cfrac%7Bx+%2B+5+-+9%7D%7B%7B%28x+-+4%29.%28+%5Csqrt%7Bx+%2B+5%7D++%2B+3%29%7D++%5C%3A+%7D++%3D++%5Cfrac%7Bx+-+4%7D%7B%7B%28x+-+4%29.%28+%5Csqrt%7Bx+%2B+5%7D++%2B+3%29%7D++%5C%3A+%7D+)
![\frac{1}{( \sqrt{x + 5} + 3) } \frac{1}{( \sqrt{x + 5} + 3) }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B%28+%5Csqrt%7Bx+%2B+5%7D++%2B+3%29+%7D+)
as x→4 this expression tends to
![\frac{1}{ \sqrt{4 + 5} + 3} = \frac{1}{6} \frac{1}{ \sqrt{4 + 5} + 3} = \frac{1}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B+%5Csqrt%7B4+%2B+5%7D++%2B+3%7D++%3D++%5Cfrac%7B1%7D%7B6%7D+)
therefore
lim x → 4
![\frac{ \sqrt{x + 5} - 3 }{x - 4} = \frac{1}{6} \frac{ \sqrt{x + 5} - 3 }{x - 4} = \frac{1}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csqrt%7Bx+%2B+5%7D+-+3+%7D%7Bx+-+4%7D++%3D++%5Cfrac%7B1%7D%7B6%7D+)
by this presses you can get answer
what is the the limit of
as x approaches 4
sol .
let's multiplying both side numerator and denominator of the expression by
to get rid to undefined
value
assuming is not equal to 4
then
as x→4 this expression tends to
therefore
lim x → 4
by this presses you can get answer
Answered by
20
HEY THERE!!
lim {√(x+5) -3}/x-4
x->4
rastionalising it we get,
lim(√(x+5) -3)/(x-4 )× (√(x+5) +3)/(√(x+5)+3)
x->4
lim( (x+5) - 3²)/(x-4)((√x+5) +3)
x->4
lim (x+5 -9)/(x-4)((√x+5)+3)
x->4
lim (x-4)/(x-4)((√x+5)+3)
x->4
lim 1/(√(x+5)+3)
x->4
now put x = 4 and the limiting value is
=> 1/(√4+5)+3)
=> 1/6
the limiting value is 1/6
________________________________________
#Thanks
Similar questions